Prácticas y conductas sexuales: factores de riesgo en jóvenes universitarios en la Facultad de Jurisprudencia, Ciencias Sociales y Políticas de la UEB, 2023-2024. - Cabezas Mishquero Sebastián Alejandro (2024)
This research paper analyzes the risk factors associated with the sexual practices and behaviors of university students at the Faculty of Law, Social Sciences, and Politics of the State University of Bolívar during the 2023-2024 period. Concern for the sexual health of this population motivated the study, given its impact on the personal and social development of the students. Despite the existence of studies on sexual dynamics in various demographic groups, specific research on university students, particularly in this context, is scarce. The study is based on a mixed-methods approach, with structured surveys collecting real demographic data and sexual behaviors. The results revealed that inappropriate sexual behaviors among students pose risks to their health, including sexually transmitted infections and early fertility. Multiple risk factors influencing these practices were identified. Additionally, a lack of information and awareness about sexual health was observed, increasing the vulnerability of university students. The conclusions emphasize the need to develop and implement effective intervention and prevention strategies. It is proposed to promote safe and responsible sexual practices through adequate sexual education, addressing both biological and sociocultural aspects. These strategies aim to improve the sexual health and general well-being of young people, contributing to a healthier and more aware university community. The study provides a comprehensive view of the risk factors associated with the sexual practices of university students, offering recommendations for future research and practices in this field.. Keywords: Infections, sexually transmitted, practices, sexual behaviors, risks, prevention.